PERAN MAHASISWA HUKUM EKONOMI SYARIAH DALAM PENGEMBANGAN KUALITAS UMKM PONDOK PESANTREN - Jamaludin; Rashif, Fauzan; Maulana, Raihan; Rifal Hilmawan, Fazri (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2025)
As a country with the largest Muslim population in the world, Indonesia has the potential to become the center of the world's halal industry. With the Muslim population reaching 85% of the total population, this could be a supporting factor for success. However, the reality is that until now the potential has not been realized. One of the areas with a large Muslim population in Indonesia is Banten Province. There are 4,579 Islamic boarding schools that can be collaborated with as facilitators of halal development. The aim of this research is to see the effectiveness of collaboration between students, Islamic boarding schools and MSMEs in order to increase the number of halal certifications in Banten. Research that collaborates with this service takes the form of providing training and education for the community, such as skills training, workshops or seminars regarding the halal certification registration process in the Islamic boarding school environment. The activity, which was accompanied by 4 HES students, resulted in 59 halal certificates. The certificate consists of food and drinks. Starting from tea, cilok, contemporary food and so on. The result of this activity is that the department needs to pay attention to continuing to socialize and educate so that students are active in these activities. Indirectly, this program also helps departments for student tracer studies which have an impact on department accreditation. Active collaboration from various parties is very necessary. So it has a positive impact on major students and MSME players